Deciphering Sex-Specific Differentiation of Human Fetal Gonads: Insight From Experimental Models - Lundgaard Riis, Malene; Jørgensen, Anne (Frontiers in Cell and Developmental Biology, 2022)
Sex-specific gonadal differentiation is initiated by the expression of SRY in male foetuses. This promotes a signalling pathway directing testicular development, while in female foetuses the absence of SRY and expression of pro-ovarian factors promote ovarian development. Importantly, in addition to the initiation of a sex-specific signalling cascade the opposite pathway is simultaneously inhibited. The somatic cell populations within the gonads dictates this differentiation as well as the development of secondary sex characteristics via secretion of endocrine factors and steroid hormones. Opposing pathways SOX9/FGF9 (testis) and WNT4/RSPO1 (ovary) controls the development and differentiation of the bipotential mouse gonad and even though sex-specific gonadal differentiation is largely considered to be conserved between mice and humans, recent studies have identified several differences. Hence, the signalling pathways promoting early mouse gonad differentiation cannot be directly transferred to human development thus highlighting the importance of also examining this signalling in human fetal gonads. This review focus on the current understanding of regulatory mechanisms governing human gonadal sex differentiation by combining knowledge of these processes from studies in mice, information from patients with differences of sex development and insight from manipulation of selected signalling pathways in ex vivo culture models of human fetal gonads.